Prestressing of NSM steel strands to enhance the structural performance of prestressed concrete beams - Obaydullah, M.; Jumaat, Mohd Zamin; Alengaram, Ubagaram Johnson; Darain, K.M.U.; Huda, M.N.; Hosen, M.A. (Elsevier, 2016)
Prestressing of strengthening materials can enhance the performance of strengthened structures as the materials become more efficient as a greater portion of their tensile capacity is employed. Prestressed concrete beams are widely used in the construction field, however, there is a lack of studies on the strengthening of these structural elements. This paper presents an experimental study on strengthening prestressed beams using near surface mounted (NSM) prestressed steel strands. A total of seven prestressed beams were constructed for static testing, with one unstrengthened control beam, one beam strengthened with a non-prestressed NSM steel strand, and five beams strengthened with NSM steel strands prestressed to varying levels of their nominal tensile strength. The structural behavior and failure modes of these specimens were investigated and the differences in performance due to the effect of the prestressing force in the NSM strands were analyzed. Based on the results, applying prestress force provides an increase in load carrying capacity with corresponding higher concrete cracking and steel yielding initiations when compared to beams strengthened with no added prestress force. The influence of various prestress levels on the deflection of the tested beams was also assessed, and the relevant results were presented and discussed. The test results showed that the strengthened prestressed beam with a 70% prestressed steel strand performed better compared to the other strengthened beams. The first crack load, yield load and ultimate load of the prestressed beam strengthened with a 70% prestressed steel strand increased by 40%, 57% and 40%, respectively, compared to the control beam.